An Estimate of Plasma Volume Changes Following Moderate-High Intensity Running and Cycling Exercise and Adrenaline Infusion - Bjerre-Bastos, Jonathan J.; Sejersen, Casper; Bihlet, Asger R.; Secher, Niels H.; Mackey, Abigail L.; Kitchen, Carl-Christian; Drobinski, Patryk; Thudium, Christian S.; Nielsen, Henning Bay (Frontiers in Physiology, 2022)
Introduction: Plasma volume (PV) changes in response to physical activity, possibly as a consequence of adrenergic activation. We estimated changes in PV in response to common exercise modalities; cycling and running as well as adrenaline infusion and a control at rest. Methods: On separate days, forty circulatory healthy subjects (aged 60 years (range: 42-75)) with knee osteoarthritis underwent moderate-high intensity cycling, running and intravenous adrenaline infusion to mimic the circulatory response to exercise. Blood samples were obtained from peripheral vein taken at several pre-defined time-points before, during, and after the interventions. PV changes were estimated using venous hemoglobin and the derived hematocrit. The temporal associations between PV and selected biomarkers were explored. Results: Changes in PV was observed during all four interventions and the response to cycling and running was similar. Compared to rest, PV decreased by -14.3% (95%CI: -10.0 to -18.7) after cycling, -13.9% (95%CI: -10.9 to -17.0) after running, and -7.8% (95%CI: -4.2 to -11.5) after adrenalin infusion. Conclusion: PV decreased in response to moderate-high intensity running and cycling. Adrenaline infusion mimicked the PV change observed during exercise suggesting separate influence of autonomic control on blood volume homeostasis. In perspective, a temporal association between PV and biomarker dynamics suggests that consideration of PV changes could be relevant when reporting plasma/serum constituents measured during exercise, but more research is needed to confirm this.